(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Svirs’ka Z. M. The problems of the content and structure improving of literature curriculum and textbooks in coverage of E. Pasichnyk. The article is an attempt to highlight the systematic approach of the concept of humanitarian education school by the founder of method of teaching Ukrainian literature - professor E. Pasichnyk. The author focuses on the principles of creating content, structure of textbooks and role of curriculum documents as a constant part of pupils literature development.